2005
DOI: 10.1093/ndt/gfi207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of renal disease in Romania: a 10 year review of two regional renal biopsy databases

Abstract: The present data are an important contribution to the epidemiology of renal diseases in Europe, highlighting not only numerous similarities but also significant epidemiological differences in Western and Central European countries, particularly a higher, albeit declining, incidence and prevalence of membranoproliferative GN. This report represents the basis for the future of Romanian Registry of Renal Biopsies and is intended to serve as a source of information for nephrologists concerned with East European re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
126
11
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(172 citation statements)
references
References 12 publications
27
126
11
8
Order By: Relevance
“…This finding was in accordance with the studies including large series of biopsies. [2][3][4] Similar with the studies in the literature including large series of biopsies, this study as well showed that the glomerular diseases were more frequent among males. 2,3,6,7 No significant difference was found between the patients with primary and secondary GN in terms of gender and age.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding was in accordance with the studies including large series of biopsies. [2][3][4] Similar with the studies in the literature including large series of biopsies, this study as well showed that the glomerular diseases were more frequent among males. 2,3,6,7 No significant difference was found between the patients with primary and secondary GN in terms of gender and age.…”
Section: Discussionsupporting
confidence: 82%
“…Primary GNs are more common than secondary GNs. [2][3][4] The presence of an underlying secondary reason that would change the therapy approach should be investigated in each glomerular disease independent from its investigated. All of the biopsy samples were obtained from to the native kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Since 128,057,352 people resided in Japan in 2010, the estimated rate of renal biopsy was 140.6 to 164.0 per million population. This rate was higher than that in Romania [24], Spain [25], the Czech Republic [10], Denmark [26], and Scotland [27], was similar to that in France [28], and was lower than that in USA, Finland [29], and Australia [30].…”
Section: Discussion and Commentsmentioning
confidence: 58%
“…In addition, data from local or limited national registries of renal biopsy have been reported from South Korea [10,11], Bahrain [12,13], Brazil [14], Romania [15], China [16], Finland [17], Serbia [18], Pakistan [19] and Belgium [20]. Finally, there are also reports that include epidemiological data only on glomerular diseases from Australia [21], Macedonia [22], France [23], USA [24], Iran [25], Germany [26], Lebanon [27], Peru [28] and Poland [29].…”
Section: Introductionmentioning
confidence: 99%